PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DAN KUALITAS LAYANAN TERHADAP PEMBELIAN ULANG MELALUI WORD OF MOUTH SEBAGAI VARIABEL MEDIASI (Studi pada Pelanggan Alfamart di Kecamatan Banyumanik, Kota Semarang) - Yuristika, Mia; Farida, Naili; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
The application of the program a relationship marketing part of customer relationship management in business approaches to affect the habit of customers through good communication will create word of mouth and can increase repurchase decision. Especially in the field of retail, the quality of services will be one of the consideration of the person before decide to choice. Alfamart observance of some aspects of competition to win in the retail business.This research supported by decreasing rank Alfamart’s top brand. The aim of this research is to find out the customer relationship management and quality service to repurchase decision through word of mouth on customers Alfamart. The method of this research is explanatory with multi stage sampling technique and taken 100 people as a Kartu AKU user. Quantitative analysis is a technique used to test the validity, reliability, coefficient correlation, coefficient determination, simple regression analysis and multiple regression analysis, significance tests (t test and f test), and path analysis.The research results show that the variable customer relationship management and service quality in a partial influence word of mouth and repurchase decision, but simultaneously only affect the repurchase decision. Variable word of mouth partial evaluation repeated affect the purchase , but not proved as variable mediation for the purchase of repeated if tested simultaneously.Suggestions that can be given in this research among others the company expected to provide training to employees on product knowledge, more attention to the convenience of shopping place, increase experience kartu AKU users, and especially about how to handling customer complaints.